2017
DOI: 10.1016/j.palaeo.2016.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Holocene environmental history of a small Mediterranean island in response to sea-level changes, climate and human impact

Abstract: To cite this version:Yoann Poher, Philippe Ponel, Frederic Medail, Valérie Andrieu-Ponel, Frédéric Guiter. Holocene environmental history of a small Mediterranean island in response to sea-level changes, climate and human impact. Palaeogeography, Palaeoclimatology, Palaeoecology, Elsevier, 2017, 465, Part A, pp.247-263.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 89 publications
8
22
0
Order By: Relevance
“…This vegetation pattern is the results of more complex environmental dynamics triggered by a decrease in the rate of sea level rise that determined deep geomorphic and sedimentological changes in the river floodplains, consistent with coastal barrier accumulation, lagoon habitat formations, river mouth modifications, and peat deposition among others (Di Rita et al, 2015). The regional woodlands were mostly composed of evergreen Quercus forests and Ericaceae scrublands, rich in other evergreen elements such as Quercus suber, Olea, Pistacia and Arbutus, as also documented in other coastal sites of Sardinia and Corsica at that time (Reille, 1992;Beffa et al, 2016;Currás et al, 2017;Poher et al, 2017). Significant frequencies of Chenopodiaceae (9%), accompanied by occurrences of foraminiferal linings and dinocysts, suggest the local presence of a salt-marsh environment, whose development was influenced by sea water input into the sedimentary basin, as also reported in many other coastal sites in the central Mediterranean region (Bellotti et al, 2011;Di Rita, 2013;Di Rita and Melis, 2013;Poher et al, 2017).…”
Section: Pollen Analysismentioning
confidence: 78%
“…This vegetation pattern is the results of more complex environmental dynamics triggered by a decrease in the rate of sea level rise that determined deep geomorphic and sedimentological changes in the river floodplains, consistent with coastal barrier accumulation, lagoon habitat formations, river mouth modifications, and peat deposition among others (Di Rita et al, 2015). The regional woodlands were mostly composed of evergreen Quercus forests and Ericaceae scrublands, rich in other evergreen elements such as Quercus suber, Olea, Pistacia and Arbutus, as also documented in other coastal sites of Sardinia and Corsica at that time (Reille, 1992;Beffa et al, 2016;Currás et al, 2017;Poher et al, 2017). Significant frequencies of Chenopodiaceae (9%), accompanied by occurrences of foraminiferal linings and dinocysts, suggest the local presence of a salt-marsh environment, whose development was influenced by sea water input into the sedimentary basin, as also reported in many other coastal sites in the central Mediterranean region (Bellotti et al, 2011;Di Rita, 2013;Di Rita and Melis, 2013;Poher et al, 2017).…”
Section: Pollen Analysismentioning
confidence: 78%
“…One possible explanation for the increased presence of anthropogenic indicators at the same time as a forest decline in response to a climate change towards aridity is that a dry event may have spurred the expansion of agriculture and the diffusion of human settlements in southern Italy and Sicily by thinning the woodland, thereby aiding its clearance by farmers (Magri, 1995;Yll et al, 1997;Lawson et al, 2004). Archeological evidence indicates that the beginning of the Neolithic era occurred earlier in dry areas of Sicily and southern Italy (Natali and Forgia, 2018) than in comparatively wetter areas of central and northern Italy (Radi and Petrinelli Pannocchia, 2018). In addition, ecosystems and vegetation were less resilient and more vulnerable to human disturbance with increasing heat and drought along a northsouth gradient.…”
Section: Discussionmentioning
confidence: 99%
“…12. Greco Pond is a coastal wetland located on Cavallo Island (Lavezzi archipelago; Corsica) (Poher et al, 2017). Mean annual precipitation is ca.…”
Section: Lago Padulementioning
confidence: 99%
“…Analysis of coleopteran fossils preserved in a 7000 year sedimentary record showed that 60% of past wetland beetle fauna became locally extinct as a result of regime shift in this freshwater pond. The largest impoverishment occurred 3700 years ago when the relative Mediterranean sea-level rose more than 1.5 ± 0.3 m (Poher et al 2017a).…”
Section: Impact Of Sea-level Risementioning
confidence: 98%